The evolving virtual library, visions and cases studies, de Laverna M. Saunders (Revista de Biblioteconomia de Brasília, 1996)
SAUNDERS, Laverna M. (ed.). The evolving virtual library, visions and cases studies. Medford, NJ : Information Today, 1996.153 p.